Evaluation of Primary and Secondary Free Flap Desyndactylization Techniques in Hand and Digit Reconstruction: A Systematic Review - Gehring, Michael B.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery Open, 2020)
Objective Injuries of the hand often require free flap reconstruction. To minimize flap loss, evidence exists to surgically syndactylize digits when repairing multiple injuries, with delayed flap division, or desyndactylization. However, evidence suggests that division of the flap at the time of inset can be accomplished with minimal negative effect. The purpose of this study was to evaluate outcomes, following hand reconstruction with free flaps utilizing either acute or staged desyndactylization techniques.Methods A systematic review utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was performed. Articles that described the use of a free flap for surgically syndactylized digits or multilobed flaps for coverage of multiple digits were included.Results One hundred sixty-one articles were reviewed with 34 fulfilling inclusion criteria. One hundred seventeen patients underwent 145 free flap reconstructions. Traumatic avulsions (49%) were the most common injuries, followed by burns (11%). Twenty-one (62%) papers described surgical syndactylization of digits, which were later desyndactylized and five (15%) papers included reconstruction of more than one digit with multilobed free flaps. Eight papers (24%) described both techniques. Overall, 100% of included flaps survived. Total complication rate was 6%, with six complications (67%) occurring in flaps with primary syndactylization.Conclusion Hand defects often require free flaps for reconstruction. Although free flaps for the reconstruction of digital defects is technically demanding, they result in better outcomes. With available evidence indicating complications rates less than those of staged desyndactylization, multidigit reconstruction with multilobed free flaps may be a more desirable technique.
Keywords: surgical syndactylization; multilobe free flaps; hand reconstruction